PEMANFAATAN WEBSITE PENJUALAN LUKISAN SEBAGAI MEDIA KOMUNIKASI PEMASARAN DI DESA TAKMUNG KECAMATAN BANJARANGKAN KABUPATEN KLUNGKUNG - I Putu Adi Saskara; I Gusti Ayu Jatiana Manik Wedanti; Ida Bagus Komang Sindu Putra (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2023)
Takmung village is one of several in the Klungkung area. Takmung Village has a popular tourist destination known as "Nyoman Gunarsa Classical Painting Museum," which is famous for its paintings. However, Takmung Village itself is less known to the public as a village of artists. In contrast to Kamasan Village, Takmung Village's artists are much less known, and many of them do not have their stalls or time to sell their artworks. The use of websites comes in handy in this problem, which helps artists to advertise their services and sell their artwork online. Aside from providing information and selling its products, a website works as an indirect representation of its professionalism and legitimacy. In addition to the local artist, it helps introduce other artists. Therefore, by utilizing the art on this website, artists from various parts of the Klungkung district can also become famous. This study created the Griya Art House, an art gallery, implementing the Research and Development methodology as its foundation. Data Flow Diagrams and Entity Relationship Diagrams are used in this study's website creation procedure. The final result of this study stated that the effectiveness of the sales website on the purchasing power of paintings was demonstrated to be effective with a total of three product purchases. The creation of this website is expected to be able to contribute to the community in Takmung Village, Banjarangkan District, Klungkung Regency, especially artists as assistance in the form of website applications that are applied in marketing their work.